Pengaruh Model Pembelajaran Kelompok Kecil Terhadap Kreativitas Siswa Kelas V SD Islamiyah Tahun Ajaran 2022/2023 - Rizkya Febrianti; Thessa Herdyana; Leni Malinda (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was carried out in class V of Islamiyah Private Elementary School with the aim of finding out the influence of the Small Group Learning Model on the Learning Creativity of Class V of Islamiyah Elementary School Students for the 2022-2023 Academic Year. The samples taken in this research were Class V of the Islamiyah Private Elementary School, Class V A as the Control Class and Class V B as the Experimental Class. Test results regarding the influence of the Small Group Learning Model (X) and Student Learning Creativity (Y) in class V of Islamiyah Private Elementary School for the 2022/2023 Academic Year. The influence of using the Small Group Learning Model has been proven from the results of research conducted on Class V students of Islamiyah Elementary School. The 2022/2023 academic year provides positive results. The results showed that the Small Group Learning Model was in the good category, and this result was also followed by student learning creativity being included in the good category with an average score for the experimental class of 82.2. It is known that by calculating the variable X, the average value is 82.2 and the standard deviation is 9.06. And variable Y obtained an average value of 51.67 and a standard deviation of 7.81. From the calculation of the hypothesis price th = 0.06, the significance of the hypothesis coefficient is consulted with the calculated t value table. The t table value with N = 60 at the 5% significance level = 0.245. This turns out to be 0.245 >. 0.06 This proves that the hypothesis is accepted. From the results of hypothesis testing using the product moment correlation formula, it is found that tcount > ttable so that Ha is accepted, Ho is rejected. So there is an influence on student learning creativity using the Small Group Learning Model.